2003
DOI: 10.1161/01.str.0000077927.63758.b6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pressure–Flow Velocity Relationships in the Human Cerebral Circulation

Abstract: Background and Purpose-The pressure-flow velocity relationship in the cerebral circulation is characterized by the critical closing pressure (CCP), which is the pressure at which flow ceases, and the linear slope of a plot between pressure and flow velocity. It has been suggested, but not validated, that CCP can be determined from arterial blood pressure (ABP) and transcranial Doppler (TCD) recordings during the cardiac cycle. We studied a group of patients in whom ventricular fibrillation (VF) was induced. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
133
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 29 publications
2
133
1
2
Order By: Relevance
“…However, strength of correlation was weaker than the correlation between CCP LDF and CCP TCD . It was undoubtedly lower than documented by Aaslid et al (2003), where comparison of CCP waveform and CCP calculated from 'long diastole' decrease in mean ABP and FV resulted in correlation generally greater than R = 0.9. Values of CCP waveform are greater than values of CCP TCD and CCP LDF .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, strength of correlation was weaker than the correlation between CCP LDF and CCP TCD . It was undoubtedly lower than documented by Aaslid et al (2003), where comparison of CCP waveform and CCP calculated from 'long diastole' decrease in mean ABP and FV resulted in correlation generally greater than R = 0.9. Values of CCP waveform are greater than values of CCP TCD and CCP LDF .…”
Section: Discussioncontrasting
confidence: 55%
“…These values were compared with CCP assessed from the TCD and ABP waveforms just before cardiac arrest adopting the algorithm of Aaslid (1992) and Aaslid et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…This method renders a CrCP that is bounded to be nonnegative. The impedance method has excellent agreement with the traditional method, except for instances where the traditional method renders clearly nonsensical low and negative values (16,17). In these cases, the new method gave results that made sense (4,18).…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies have provided preliminary data and validation of this concept [14]. Using a bench model [15], we have shown that despite large variability in ZFP values obtained with different configurations of flow velocity and blood pressure pulsatility, this method can be reliably used to assess changes in CPP and ZFP.…”
Section: Discussionmentioning
confidence: 92%